Efficacy and Safety of Tildrakizumab in a Patient with Chronic HBV Infection - Potestio L; Piscitelli I; Fabbrocini G; Martora F; Ruggiero A; Megna M (Dove Medical Press, 2023)
Luca Potestio, Ilaria Piscitelli, Gabriella Fabbrocini, Fabrizio Martora, Angelo Ruggiero,* Matteo Megna* Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Angelo Ruggiero, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini, 5, Naples, 80131, Italy, Tel +39 - 81 -7462457, Fax +39 - 81 - 7462442, Email Angeloruggiero1993@libero.itAbstract: The introduction of biologic drugs revolutionized the management of moderate-to-severe forms of psoriasis. However, safety concerns still remain, particularly on patient affected by opportunistic infections. In this scenario, the safety of biologic drugs in patient with HBV infection is debated. Globally, screening for hepatitis before starting biological treatment is mandatory as well as a referral to an infectivologist and eventual prophylactic management should be evaluated case by case, also considering risk factors. On the one hand, the use of anti-Tumor Necrosis Factor seems to increase the risk of HBV reactivation, conversely, the use of recently approved classes of biologics [anti-interleukin (IL) 17 and anti-IL23] seems to have a lower risk of HBV reactivation. However, the evidence on the safety of anti-IL23 drugs in patients affected by HBV is scant, particularly for patients undergoing treatment with tildrakizumab. Herein, we report the first case of a female patient affected by moderate-to-severe psoriasis and with chronic HBV infection undergoing prophylaxis, successfully treated with tildrakizumab without reporting hepatitis reactivation. Even if limited, our case seems to confirm available evidence about the safety of anti-IL23, particularly tildrakizumab, on patients with chronic HBV infection undergoing prophylaxis.Keywords: psoriasis, HBV infection, biologic therapy, anti-IL23, tildrakizumab